Assessing the role of the KISS1 receptor in breast cancer cell behaviour with the use of CRISPR-mediated gene editing - Van den Bout, Jan Iman (University of Pretoria, 2023)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2023.